Consequences of Scapular Anatomy for Reversed Total Shoulder Arthroplasty - Middernacht, Bart (Springer-Verlag, 2008)
The reverse total shoulder prosthesis provides successful functional outcome in many patients with rotator cuff tear arthropathy. However, scapular notching, a direct consequence of mechanical impingement between the humeral prosthesis and the glenoid, remains a major concern. We presumed a better knowledge of the anatomy of the scapula would enable design or placement modifications to minimize this phenomenon. After establishing a uniform spatial reference system using easy locatable surgical reference points and planes, we analyzed 200 dry bony scapulae and defined the glenoid and infraglenoid anatomy relative to the reference system. The bony rim of the two inferior quadrants of the glenoid forms a semicircle the center of which can be used perioperatively as an easy locatable bony reference point. The infraglenoid tubercle varies in width and length, and can interfere with the humeral part of the reverse prosthesis, creating scapular notching. To avoid notching, we suggest using a convex base plate with a smaller radius than currently used, placing it as low as possible with a 42-mm glenosphere eccentrically assembled to create a posterior offset. If prosthetic overhang cannot be obtained, we suggest removing part of the infraglenoid tubercle.